Pruritus in Uremic Patients: Approaches to Alleviating a Common Symptom in Chronic Kidney Disease - Ștefania Cîrstea; Olguța Anca Orzan; Diana Silvia Zilișteanu (Life, 2025)
Chronic kidney disease-associated pruritus (CKD-aP) is a distressing symptom that affects both dialysis and non-dialysis patients, significantly impairing their quality of life. Despite its multifactorial pathophysiology, no gold-standard treatment has been established. This review explores various therapeutic options and evaluates their effectiveness based on recent clinical studies and meta-analyses. Therapies targeting novel mechanisms have evolved in recent years. Difelikefalin, a κ-opioid receptor agonist, represents a breakthrough in systemic treatment, demonstrating efficacy with a favorable safety profile. Another opioid-based therapy, nalfurafine, has shown notable symptom relief in multiple clinical studies, with a low risk of abuse. Sertraline, an antidepressant, offers another alternative, although its delayed onset remains a limitation. Nonpharmacologic approaches are also evolving. Phototherapy, particularly UV-B therapy, modulates the immune response, reduces inflammation, and effectively alleviates itching in hemodialysis patients. Personalized treatment strategies are crucial, as responses vary among patients. Further research, including comparative and long-term studies, is essential to refine treatment algorithms and improve patient outcomes. By integrating new pharmacologic and nonpharmacologic options, CKD-aP management is shifting toward a more tailored and effective approach that addresses the individual needs of each patient.